The Effect of the Pentrich Model on the Cognitive Achievement of International Law Subjects of Handball for Students - Kadhem, Abbas Abdulhamza; Mahdi, Dheyaa Mohammed; Hussien, Abeer Ali (Journal of Social Work and Science Education, 2022)
The importance of the research was to prepare educational units according to the Pinterch model for the subjects of international law handball for students and to identify the effect of those units on the cognitive achievement of the subjects of international law handball for students of the experimental group. As the research problem was represented in the researcher’s attempt to delve into and use the Pinterch model to provide students with the knowledge side of the subjects of international law in handball because the law contains overlap and situations that the student cannot master except through the use of modern methods and methods where the learner has the freedom to choose what he learns and in the way that It suits it, so the researcher tried to use this model as a step to address the weakness in the cognitive side of the international law of handball for students. While the objectives of the research were to prepare educational units according to the Pintersch model for the subjects of international law handball for students. As well as identifying the effect of educational units according to the Pinterch model in the cognitive achievement of the subjects of international law handball for students of the experimental group.